THU0187 Does Ultrasound-Scored Synovitis Depend on the Pharmacokinetics of Subcutaneous Anti-TNF Agents in Patients with Rheumatoid Arthritis?. (10th June 2014) - Hinojosa-Dávila, M.; Naredo, E.; Valor, L.; Hernández, D.; Mata-Martínez, C.; Serrano-Benavente, B.; Bello, N.; Ovalles-Bonilla, J.G.; Martínez-B., J.; Martínez-E., L.; Nieto, J.C.; Del Río, T.; et al.
Abstract : Background: Many observational studies have shown responsiveness of ultrasound (US)-detected synovitis in rheumatoid arthritis (RA) patients, most of them using biologic therapies. However, these studies have not taken into consideration in their design the pharmacokinetic characteristics of the drug administered. Objectives: To investigate whether the pharmacokinetics (i.e. time point of US assessment) of subcutaneous anti-Tumour Necrosis Factor (anti-TNF) agents influences the grade of US-detected synovitis in RA patients treated with these drugs. Methods: Fifty consecutive RA patients (31 women, 18 men) were prospectively recruited from the Biologic Therapy Unit of our hospital. Inclusion criteria consisted of being in treatment with subcutaneous anti-TNF agents and having had neither changes in therapy nor local corticosteroid injections in the previous 3 months. Patients underwent clinical, laboratory and US assessment at two time points, i.e., at peak plasma drug concentration and at trough plasma drug concentration. Patients were assessed at both time points for disease activity according to the Disease Activity Score in 28 joints (DAS28) and the Simplified Disease Activity Index (SDAI) by the same investigator. US assessments were performed by a rheumatologist expert in musculoskeletal US who was blinded to the anti-TNF agent, the administration time, and the clinical and laboratory data. Twenty-eight joints were investigated for the presence and grade (0-3) of B-mode synovitis and synovial PD signal (i.e. Doppler synovitis). A global index for B-mode synovitis (BSI), joint count for B-mode synovitis (BSC), a global index for Doppler synovitis (DSI), and joint count for Doppler synovitis (DSC) were calculated for a 12-joint US scoring model (31) and a wrist-hand-ankle-foot US scoring model. B-mode US remission was defined as a BSI <1 and Doppler US remission as a DSI <1. Results: Twenty (40.8%) patients were treated with etanercept, 19 (38.8%) with adalimumab, 6 (12.2%) with golimumab, and 4 (8.2%) with certolizumab. There were no significant differences between the clinical, laboratory and B-mode and Doppler US indices and joint counts for both the 12-joint US model and the wrist-hand-ankle-foot model at peak time and trough time (p=0.132-0.986). There were no significant differences between the proportion of patients with active disease and those in remission according to DAS28, SDAI, B-mode US, and Doppler US at peak time and trough time assessments (p=0.070-1). DAS28, Disease Activity Score in 28 joints; SDAI, Simplified Disease Activity Index; B-mode synovitis index; BSC, B-mode synovitis count; DSI, Doppler synovitis index; DSC, Doppler synovitis count; W, wrist; A, ankle; Diff, values at peak time–values at trough time. Conclusions: Our results suggested that subcutaneous anti-TNF pharmacokinetics does not significantly influence US-scored synovitis in RA patients. Disclosure of Interest: : M. Hinojosa-Dávila: None declared, E. Naredo Grant/research support: Esperanza Naredo has received speaker fees from Abbvie, Roche Farma, Bristol-Myers Squibb, Pfizer, UCB, General Electric Healthcare, and Esaote. Esperanza Naredo has received research funding from UCB and MSD., L. Valor: None declared, D. Hernández: None declared, C. Mata-Martínez: None declared, B. Serrano-Benavente: None declared, N. Bello: None declared, J. G. Ovalles-Bonilla: None declared, J. Martínez-B.: None declared, L. Martínez-E.: None declared, J. C. Nieto: None declared, T. Del Río: None declared, C. González: None declared, J. Lόpez-Longo: None declared, M. Montoro: None declared, I. Monteagudo: None declared, L. Carreño: None declared DOI: 10.1136/annrheumdis-2014-eular.2966